Sejarah Sosial Terbentuknya Kabupaten Pasangkayu - Usman, Rahmadi (Jurnal Ilmiah Multidisiplin Amsir, 2023)
The aim of this research is to find out the form of community struggle to develop Pasangkayu into a district. To find out the community's social conditions after the formation of Pasangkayu Regency. And to find out about community developments after the name change of North Mamuju Regency to Pasangkayu Regency. This research method uses historical research methods, namely 1. Heuristics (data collection). 2. Source criticism is divided into two types, namely external and internal criticism. 3. Interpretation (data analysis) of various information obtained from various sources. 4. Historiography is intended to write historical events in the form of scientific work using descriptive language and explanations. The research results show that the formation of North Mamuju Regency was based on natural resource factors and the community's inability to view Mamuju Regional Government services as favoritism. Finally, a movement initiated by the people of Sarudu Village was carried out, resulting in a forum called KAPKP (Action Committee for the Establishment of Pasangkayu District) to fight for these ideals. The peak of the struggle, on July 4, 2002, was the expansion of North Luwu Regency.